The litigation between Greenhalgh and the Mallard family, [1941-1950]: and its influence on company law in England, Australia and South Africa - Smith, Charles Adamson (Department of Commercial Law, 2021)
On 1 July 1941 Mr Greenhalgh issued a writ against his co-shareholders in the Arderne Cinema Company, and thus began a series of cases which ended with a Court of Appeal Judgment handed down on,10 November 1950. During the almost ten-year period of the litigation, seven actions were brought by Mr Greenhalgh, five of which were taken on appeal. Mason1 writing in the Australian Law Journal said of the litigation "It thus represents something of an epic of litigious heroism· while Professor Sealy2 in a note in the Cambridge Law Journal dealing with the Clemens case3 in referring to a seemingly wide choice of remedies .... available to a minority through the courts ... remarks that many of them have a sorry history as the ghost of Mr Zuccani ...., Mr Sidebottom ...., Mr Greenhalgh .... and the many other unsuccessful litigants who haunt the pages of the textbooks could plainly testify." The first two references are to Allen v Gold Reefs of West Africa [1900] 1 Ch.656 and Shuttleworth v Cox Bros. & Co. (Maidenhead) [1927] 2 K.B. 9, of which more later and the third, of course, to Mr Greenhalgh of the Arderne Cinema company. D D Prentice4 In a Law Quarterly Review article entitled 'Restraints on the Exercise of Majority Shareholder Power' begins with the words: "The plight of Mr Greenhalgh is known to all students of company law and his fate has been held up as a salutary warning to all minority shareholders who have the temerity to do battle with the big battalions." Gower in Principles of Modern Company Law 4 ed (1979), referring to the last appeal, says "This last case, however, was merely the culmination of a long battle in the courts which is such an admirable illustration of the vulnerability of a minority shareholder that it is worthwhile summarising the whole story.